Sonographic measure techniques of fetal penile length - Álvaro López Soto; Jose Luis Meseguer González; Rocío López-Perez; Mónica Lorente Fernández; Juan Martínez-Uriarte; Olivia García Izquierdo (Korean Society of Obstetrics and Gynecology, 2020)
Postnatal penile length is a reliable, standardized, and widely used marker for the diagnosis of genitourinary pathology, as well as genetic and hormonal disorders. In contrast, prenatal diagnosis has not been developed equally and there is a lack of relevant literature. Our objective is to review the studies on fetal penile length, and apply findings to clinical practice. Although the most used technique is the outer penile length, there is no consensus regarding the appropriate technique for prenatal measurement. Several reports have provided reference data with high correlation. However, important issues like poor correlation with post-natal measures or presence of confounding variables are still present. Diagnosis of both a micropenis and macropenis can indicate related pathologies, and this information may benefit parental counseling and facilitate fetal management. Therefore, it is necessary to carry out prospective studies that provide reliable normative data.